Unraveling the Sclerotinia Basal Stalk Rot Resistance Derived From Wild Helianthus argophyllus Using a High-Density Single Nucleotide Polymorphism Linkage Map - Talukder, Zahirul I.; Underwood, William; Misar, Christopher G.; Seiler, Gerald J.; Liu, Yuan; Li, Xuehui; Cai, Xiwen; Qi, Lili (Frontiers in Plant Science, 2021)
Basal stalk rot (BSR), caused by the fungus Sclerotinia sclerotiorum, is a serious disease of sunflower (Helianthus annuus L.) in the humid temperate growing areas of the world. BSR resistance is quantitative and conditioned by multiple genes. Our objective was to dissect the BSR resistance introduced from the wild annual species H. argophyllus using a quantitative trait loci (QTL) mapping approach. An advanced backcross population (AB-QTL) with 134 lines derived from the cross of HA 89 with a H. argophyllus Torr. and Gray accession, PI 494573, was evaluated for BSR resistance in three field and one greenhouse growing seasons of 2017-2019. Highly significant genetic variations (p < 0.001) were observed for BSR disease incidence (DI) in all field screening tests, and disease rating and area under the disease progress curve in the greenhouse. The AB-QTL population and its parental lines were genotyped using genotyping-by-sequencing. A genetic linkage map spanning 2045.14 cM was constructed using 3,110 SNP markers mapped on 17 sunflower chromosomes. A total of 21 QTL associated with BSR resistance were detected on 11 chromosomes, each explaining a phenotypic variation ranging from 4.5% to 22.6%. Of the 21 QTL, eight were detected for BSR DI measured in the field, seven were detected for traits measured in the greenhouse, and six were detected from both field and greenhouse tests. Thirteen of the 21 QTL had favorable alleles from the H. argophyllus parent conferring increased BSR resistance.